Analysis Of Sleep Pattern In Postmenopausal Women With Knee Osteoarthritis. - Mahavir Patil, Sneha; Jadhav, Aditi (Journal of Neonatal Surgery, 2025)
Introduction- Osteoarthritis is type of degenerative disease, which is described by incremental loss in articular cartilage and peripheral bony changes which results into joint pain, swelling and osteophyte formation particularly in weight bearing joint. Additionally, adequate sleep duration for young adult recommendation is 7 ≤ 9 hours, while for elder adults it is 7 to 8 hours. As per reports, it is concluded that inflammatory factors plays important role in progression of osteoarthritis and are also interlinked with hormonal levels in postmenopausal women. Hormonal changes are the one of the reason for sleep problems in postmenopausal women and has essential role in maintaining bone metabolism. This analysis aims to investigate the sleep patterns in postmenopausal women with knee osteoarthritis, exploring the relationship between sleep quality, osteoarthritis and postmenopausal women. Methodology This cross-sectional study was conducted at D .Y. Patil Medical College Hospital and Research Institute, Kolhapur over 1.5 years. 93 postmenopausal women with knee osteoarthritis were recruited using convenience sampling. Participants were evaluated using Pittsburgh Sleep Quality Index and Lequesne Scale. Results Analysis of sleep pattern in postmenopausal women with diagnosed knee osteoarthritis is done by using SPSS software. Total 93 participants were included for this observational study out of which about 64.52% were having moderate sleep quality, 25.81% mild type sleep quality and severe sleep quality was seen in 9.68%. In terms of Knee Osteoarthritis (OA) severity about 47.31% has severe. Conclusion This study concludes that poor sleep quality is predominantly observed in postmenopausal women with knee osteoarthritis. Also the relationship between knee osteoarthritis, sleep pattern and postmenopausal women